`Self-activating' Bi3TaO7-Bi4TaO8Br photocatalyst and its use in the sustainable production of pro-fluorophoric rhodamine-110 - Banoo, Maqsuma; Chatterjee, Kaustav; Mondal, Sanjit; Vinod, C. P.; Gautam, Ujjal K. (Green Chemistry, 2022)
We counter two common notions that (i) photocatalysts are likely to degrade during use with barely any strategy to counter it and (ii) rhodamine-B (RhB) photo-degradation lacks any useful or commercial prospects even after 53 years of its discovery by developing a photocatalyst that continues to improve its activity for similar to 300 h due to a leaching induced `self-activation' process. Rhodamine-110 (Rh110) is a widely used pro-fluorophore in biological studies. However, its commercial production is highly challenging due to the formation of various side-products originating from the presence of the two labile amino side-groups that induce the pro-fluorophore activity, leading to purification difficulties, low yield, and unusually high costs. Herein, we demonstrate a facile strategy to produce pure Rh110 using extremely inexpensive RhB and Bi3TaO7-Bi4TaO8Br heterostructures as a catalyst in sunlight. The catalyst is not just stable over 30 catalytic cycles but also gets activated continuously in successive cycles to produce a reaction yield as high as 88%. The role of the heterostructure, the origin of surface activation, and the RhB -> Rh110 transformation mechanism have been established. Based on 150 days of sunlight experiments, large-scale production prospects (similar to 4000 times scale-up) and isolation of Rh110 have also been realized, paving a novel way for its production by anyone, inexpensive biological essaying, and device fabrication. Continuously improving catalysts are unknown and compensatory leaching of metal atoms from the catalyst surface may pave the way to realize them.

Covalently interconnected layers in g-C3N4: toward high mechanical stability, catalytic efficiency and sustainability - Roy, Raj Sekhar; Mondal, Sanjit; Mishra, Samita; Banoo, Maqsuma; Sahoo, Lipipuspa; Kumar, Amit; Vinod, C. P.; De, Arijit K.; Gautam, Ujjal K. (Applied Catalysis B: Environmental, 2023)
The grim prospects for the industrial utilization of g-C3N4 nanosheets arise from multi-step processing resulting in low material yields and poor visible light response due to quantum confinement. Herein, we introduce a strategy for linking the adjacent layers of g-C3N4 covalently to realize a high surface area without excess mass loss in a one-step process by introducing diethylene glycol as a precursor that produces-(CH2)2-O-(CH2)2-linkers in-situ. Their presence increases interlayer spacing and introduces surface curvatures, discouraging the stacking of a larger number of layers to produce nanosheets with-3 times higher surface area. Interestingly, unlike other layered materials, the linkers also provide extraordinary mechanical stability against exfoliating forces. In addition, the process instills sub-bandgap states and a considerable visible light response at 500 nm to slow down the picosecond exciton recombination dynamics, resulting in-5 times enhancement in H2 generation efficiency from photocatalytic water-splitting over the bulk sample.
Keywords: Layer-linkers; Sustainable synthesis; Transient absorption spectroscopy; water-splitting

Enhancing the Catalytic Activity of Pd Nanocrystals towards Suzuki Cross-Coupling by g-C3N4 Photosensitization - Mondal, Sanjit; Sahoo, Lipipuspa; Banoo, Maqsuma; Vaishnav, Yuvraj; Prabhakaran Vinod, Chathakudath; Gautam, Ujjal (Chemnanomat, 2024)
Developing renewable means of activating molecules over traditional catalysts for C-C bond formation is desirable for industrial applications. Herein, we report a strategy to improve the efficiency of Pd nanoparticles (NPs) for the Suzuki cross-coupling reactions by visible-light irradiation using g-C3N4 nanosheets (NSs) as photosensitizer. Pd NPs mounted on g-C3N4 become electron-rich under visible-light due to generation of excited electrons in g-C3N4 and thereby accelerate the rate-determining step. Remarkable photocatalytic activity was accomplished utilizing Pd/g-C3N4 for the Suzuki cross-coupling reaction in environmentally benign aqueous settings under room temperature conditions. The activity remarkably improves (similar to 2.5 times) upon light irradiation, yielding one of the highest known turnover frequencies (TOF) of 1858 h(-1) and confirming the photosensitizer role of g-C3N4. The TOF for coupling of aryl bromides is also significantly high (similar to 356 h(-1)). We establish that the low-energy/long-lived excitons preferencially transfer to Pd, paving a way for rational designing photocatalysts for various C-C coupling reactions.
Keywords: 2D graphitic carbon nitride; C-C cross-coupling; exciton transfer; heterogeneous photocatalyst; Photosensitization